First detection of Lumpy Skin Disease virus in Tunisia - Mejri, Selma; Ayari Fakhfakh, Saida Emna; Ourabi, Makrem; Abid, Amira; Zaghouani, Rahma; Nouassri, Marouène; Mhiri, Samir; Gallah, Sahbi; Habboubi, Nouha; Hosni, Kaddour; Abidi, Noura; Braiki, Nadia; et al. (Frontiers in Virology, 2025)
Lumpy Skin Disease (LSD) is an emerging bovine vector-borne disease of important economic impact on the cattle industry. Since its first identification in 1929, the disease was restricted for decades, to Sub-Saharan regions before its spread into new areas. In 2023 and 2024, LSD cases were identified for the first time in north African countries, Libya and Algeria, respectively. From June 2024, many LSD suspected cases were investigated in Tunisia. From June to October 2024, one hundred and twenty-one samples were investigated. Most of samples consist of blood samples, nasal and oral swabs from 49 suspected cattle from different parts of Tunisia. All samples were tested using Real-Time PCR and High Resolution Melting assay (HRM). On August 7, 2024, we reported the first LSD case in Tunisia. Two months later, other positive cases were confirmed by the two molecular techniques. The HRM technique allow the identification of a positive Bovine Papular Stomatitis animal presenting LSD clinical signs. Among the 49 tested cattle, eighteen were confirmed LSD positive. Most of LSD cases were from north western regions, close to Algerian border. The number of positive cases highly increased from October, period corresponding to increased LSD vectors’ activity. This is the first report on the identification of LSD in Tunisian cattle. Our findings confirm the progressive spread of LSD into new areas, and highlight the need of the implementation of control and surveillance measures to face such diseases.